Pollen viability and germinability of putative Bursera hybrids (section Bullockia; Burseraceae) in Mexico - Rico, Yessica; Reyes Estanislao, Leticia (Instituto de Ecología, A.C., 2018)
Background and Aims: The genus Bursera (~100 species) has its center of diversification and endemism in Mexico. Interspecific hybridization is a frequent phenomenon in Bursera in areas where related species coexist. Hybridization on the one hand can reinforce reproductive barriers, increase genetic variation, generate novel ecotypes and new lineages, and on the other hand, can lead to maladaptation. However, the ecological and evolutionary consequences of natural hybridization critically depend on hybrid fitness. In this study, within a putative hybrid population in the tropical dry forest of the Bajío region in Mexico and as a proxy of hybrid fitness, we investigated pollen viability among Bursera cuneata, B. bipinnata, and their putative hybrid.Methods: We used two techniques: a pollen staining test with tetrazolium chloride 1% and an in vitro germination test to observe the formation of pollen tubes. Viability percentages were calculated for each group; statistical tests were conducted with general linear models. Key results: Results demonstrated that the putative hybrid is not sterile and exhibited higher germination rates relative to the parental species. Conclusions: Our results imply that gene flow between the parental species and the putative hybrid is likely to occur. Future genetic studies should confirm the genetic identity and ploidy levels of hybrids and evaluate whether genetic introgression has occurred. Our study demonstrates that Bursera hybrids can be fertile and contributes towards understanding the role of hybridization and reproductive isolation in Mexican Bursera species.